2019
DOI: 10.1002/jhet.3634
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of Benzazolyl Azolyl Sulfamoyl Acetamides

Abstract: A new class of benzazolyl azolyl sulfamoyl acetamides was prepared from azolyl sulfamoyl acetates and benzazolyl amines in the presence of KOtBu in tetrahydrofuran. Compounds with benzothiazole‐thiazole, benzimidazole‐thiazole, benzothiazole‐imidazole, and benzimidazole‐imidazole moieties exhibited excellent antibacterial activity against Bacillus subtilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…[ 18,21 ] In fact, we have achieved N ‐sulfonylation of heteroarylamines with ethyl chloroacetate in the presence of dispersed sodium in tetrahydrofuran (THF). [ 22 ] It was observed that the reaction proceeded effectively with dispersed Na. As such, we have carried out the reaction of 15 with methyl 2‐chloroacetate in the presence of dispersed sodium under ultrasonication at a frequency of 46 kHz wherein 2‐chloro‐ N ‐[4‐(4‐chlorofuran‐2‐yl)‐1 H ‐imidazol‐2‐yl]acetamide ( 17 ) was obtained in an excellent yield.…”
Section: Resultsmentioning
confidence: 99%
“…[ 18,21 ] In fact, we have achieved N ‐sulfonylation of heteroarylamines with ethyl chloroacetate in the presence of dispersed sodium in tetrahydrofuran (THF). [ 22 ] It was observed that the reaction proceeded effectively with dispersed Na. As such, we have carried out the reaction of 15 with methyl 2‐chloroacetate in the presence of dispersed sodium under ultrasonication at a frequency of 46 kHz wherein 2‐chloro‐ N ‐[4‐(4‐chlorofuran‐2‐yl)‐1 H ‐imidazol‐2‐yl]acetamide ( 17 ) was obtained in an excellent yield.…”
Section: Resultsmentioning
confidence: 99%
“…These entities are incredibly valued in the discovery of new APIs but are often non-trivial to synthesise. As such, an optimised reaction sequence would be invaluable to both a medicinal hit-to-lead process and the scaled preparation, offering advantages over similar preparations [69,70]. In total, fourteen different benzothiazole-secondary amines (18a-n) have been generated from five different benzo-1,2,3-dithiazole 2-oxides (17a-e, Table 2); the yield varied widely, with some being as low as 8%, though there is no indication that the process was optimised.…”
Section: Formation Of Secondary 2-aminobenzothiazolesmentioning
confidence: 99%